Embolisation of a bronchial artery of anomalous origin in massive haemoptysis - Md Ralib @ Md Raghib, Ahmad Razali; Ng, Teck Han; How, Soon Hin; Muda, Ahmad Sobri (Universiti Sains Malaysia, 2010)
Massive haemoptysis is the most dreaded of all respiratory emergencies. Bronchial artery embolisation is known to be a safe and effective procedure in massive haemoptysis. Bronchial artery of anomalous origin presents a diagnostic challenge to interventional radiologists searching for the source of haemorrhage. Here, we report a case of massive haemoptysis secondary to a lung carcinoma with the bronchial artery originating directly from the right subclavian artery. This artery was not evident during the initial flush thoracic aortogram. The anomalous-origin bronchial artery was then embolised using 15% diluted glue with good results. An anomalous-origin bronchial artery should be suspected if the source of haemorrhage is not visualised in the normally expected bronchial artery location.